The Specificity of Development of Russian Literary Process - Raima Shirinova, Saodat Kamilova, (Opción, 2019)
The article is devoted to the characteristics and detailed analysis of main conceptions of contemporary Russian literary process. The conceptual models by Remizova, Ivanova, Chuprinin, and Yermolin are analyzed and generalized; personal opinion on conceptual tendencies of the development of Russian literature at the turn of the XX-XXI centuries, represented in the scheme perturbation – climate – arena, is suggested. Such approach to the systematization of literary material allowed displaying the key tendencies of the development of modern literary process in Russia. In conclusion, reflecting modern life aesthetically, modern literature anyway helps modern people to realize their place in our disordered world.